2014
DOI: 10.1007/s13277-014-1727-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between cyclin-dependent kinase inhibitor 1B rs2066827 polymorphism and breast cancer susceptibility

Abstract: In order to make a comprehensive assessment of the potential association between one genetic variant in the cyclin-dependent kinase inhibitor 1B gene, rs2066827, and breast cancer risk, we conducted a meta-analysis of six epidemiological studies, which included 3,139 breast cancer cases and 2,936 controls. The data showed that rs2066827 polymorphism was not associated with increased breast cancer risk in overall population. When stratifying by the race, no noteworthy associations were observed in Asians or Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previously, two meta-analyses investigated the association of CDKN1B gene polymorphisms (including rs34330 and rs2066827) and CDKN1B rs2066827 polymorphism with susceptibility to breast cancer, respectively3031. The previous meta-analyses found that p27 gene rs2066827 polymorphism was not associated with breast cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, two meta-analyses investigated the association of CDKN1B gene polymorphisms (including rs34330 and rs2066827) and CDKN1B rs2066827 polymorphism with susceptibility to breast cancer, respectively3031. The previous meta-analyses found that p27 gene rs2066827 polymorphism was not associated with breast cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a complex disease resulting from genetics, environmental factors and their interactions, effects the public health problem worldwide [1]. Epidemiological studies have indicated that traditional risk factors including diet rich in fat, less physical activity, smoking, and alcohol consumption contributed to the susceptibility to cancer.…”
Section: Introductionmentioning
confidence: 99%